2012
DOI: 10.1007/s10936-012-9203-9
|View full text |Cite
|
Sign up to set email alerts
|

Language Switching in the Production of Phrases

Abstract: The language switching task has provided a useful insight into how bilinguals produce language. So far, however, the studies using this method have been limited to lexical access. The present study provides empirical evidence on language switching in the production of simple grammar structures. In the reported experiment, Polish-English unbalanced bilinguals switched between their L1 and L2 while describing pictures of ongoing and completed actions with simple SV progressive and perfective phrases. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…Taken together, the study of Gullifer et al (2013) indicates that switch costs can be abolished in a sentence context, whereas Tarłowski et al (2013) showed substantial switch costs with sentences. Furthermore, sentence comprehension studies appear to be conflicting as well, with some studies finding no switch costs (Dussias, 2003;Ibáñez, Macizo, & Bajo, 2010) and other studies that do find switch costs in a sentence context (Philipp & Huestegge, in press;Proverbio, Leoni, & Zani, 2004).…”
Section: Language Switching In Sentencesmentioning
confidence: 78%
See 3 more Smart Citations
“…Taken together, the study of Gullifer et al (2013) indicates that switch costs can be abolished in a sentence context, whereas Tarłowski et al (2013) showed substantial switch costs with sentences. Furthermore, sentence comprehension studies appear to be conflicting as well, with some studies finding no switch costs (Dussias, 2003;Ibáñez, Macizo, & Bajo, 2010) and other studies that do find switch costs in a sentence context (Philipp & Huestegge, in press;Proverbio, Leoni, & Zani, 2004).…”
Section: Language Switching In Sentencesmentioning
confidence: 78%
“…This entails that in this study, responses were not measured immediately after switching from one language to another, but later on, which could have deteriorated the switch costs to the point that they were not observed anymore. Tarłowski, Wodniecka, and Marzecová (2013) also investigated language switching between sentences instead of between isolated words. Importantly, in this production study, switch costs were measured at the onset of the language switch (i.e., at the beginning of the sentence).…”
Section: Language Switching In Sentencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some evidence for the involvement of lemmas during language control comes from studies that investigated language switching with sentences instead of single words, since each lemma includes the syntactic information of the word, and sentence processing is assumed to occur at the lemma level (for a review on bilingual models of sentence processing, see Hartsuiker & Pickering, 2008). Tarlowski, Wodniecka, et al (2013), for example, asked Polish-English bilinguals to describe a scene on a picture, either in a present progressive or a present perfective phrase. Their results indicated that language switch costs can be obtained when switching between sentences (for a similar result within sentences, see Bultena, Dijkstra, & van Hell, 2015).…”
Section: The Role Of Lemmas During Language Controlmentioning
confidence: 99%